Charters of Shaftesbury Abbey - Kelly, S. E. (Anglo-Saxon charters, 2008)
The latest volume of Anglo-Saxon charters covers the pre-Conquest archive of Shaftesbury Abbey in Dorset, founded by King Alfred and destined to be of great importance in the medieval period. The majority of the thirty surviving documents date from the tenth century, with the latest a charter of Cnut from 1019. The present edition addresses the extensive corruption introduced into the surviving texts by repeated earlier copying. This is a very important collection providing almost the only evidence for the history of Shaftesbury in the Anglo-Saxon period.